Estrogen modulates 7/4 antigen distribution within eccentrically contracted injured skeletal muscle. (May 2015) - Fulkerson, ND; Nicholas, J; St. Pierre Schneider, B
Abstract Eccentric contractions are skeletal muscle stretches with concurrent active force production; these contractions commonly occur during dynamic sports activities and can cause acute muscle injury. Recovery from this injury depends in part on pro-inflammatory processes, such as neutrophil infiltration at the injured site, which is affected by estrogen. This estrogen effect has been examined broadly, but without distinguishing between major compartments within muscle in which neutrophil infiltration can occur. Therefore, we compared neutrophil antigen expression in two compartments of eccentrically contracted muscle of ovariectomized mice with or without estrogen. To quantify neutrophil antigen expression, serial cross sections of muscle were immunolabeled with antibodies that recognize 7/4 or Ly6C/G, then quantified using computer-assisted image analysis. At 48 h post injury, estrogen-positive (E+) mice had more 7/4-positive and Ly6C/G-positive myofibers, increased 7/4 area percentage, and more 7/4-positive cells in the connective tissue. In addition, E+ mice showed more 7/4-positive myofibers that were Ly6C/G-negative and more Ly6C/G-positive myofibers that were 7/4-negative. These data suggest that in injured muscle, estrogen increases 7/4 antigen in connective tissue and myofibers and is associated with more Ly6C/G-positive myofibers when the 7/4 antigen is absent from these myofibers.